2020
DOI: 10.1177/1354816620909994
|View full text |Cite
|
Sign up to set email alerts
|

The migration–tourism nexus in the EU28

Abstract: This study explores the nexus between tourism and migration on an intra-European scale over the period 2000–2015. Complex-network analysis and gravity models were the investigation methods preferred. For each year under study, we built two country-to-country networks to map and reveal the connections between states as shaped by migration stocks and tourism flows, respectively. Then, the main determinants of the correlation patterns between the two networks were investigated by several econometric analysis. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 75 publications
0
18
2
1
Order By: Relevance
“…On the one hand, Balli et al (2016), using a gravity model, report a positive relationship between migration and tourist departures (push effect). On the other hand, Provenzano (2020), using complex-network analysis and gravity model, finds no relevant indirect causal relationship in the tourism–migration nexus. However, the current stance of gravity literature tends to favor theoretically consistent structural models to avoid empirical biases (Anderson, 2011; Baldwin and Taglioni, 2006; Yotov et al, 2016).…”
Section: Introductionmentioning
confidence: 93%
“…On the one hand, Balli et al (2016), using a gravity model, report a positive relationship between migration and tourist departures (push effect). On the other hand, Provenzano (2020), using complex-network analysis and gravity model, finds no relevant indirect causal relationship in the tourism–migration nexus. However, the current stance of gravity literature tends to favor theoretically consistent structural models to avoid empirical biases (Anderson, 2011; Baldwin and Taglioni, 2006; Yotov et al, 2016).…”
Section: Introductionmentioning
confidence: 93%
“…By using several econometric analyses, he has investigated the main determinants of the correlation patterns between the two networks. This new study has concluded a quite similar topological structure for the tourism and migration networks as well as to a significant and reciprocal direct influence between tourism and migration movements inside the European Union (Provenzano, 2020). In the same sense, this study has not detected a relevant indirect causal relationship between tourism and migration nexus.…”
Section: The Empirical Studiesmentioning
confidence: 51%
“…More recently, based on an intra-European data (2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015), and by using complex-network analysis and gravity models, Provenzano (2020) has built two country-to-country networks to map the effect for each studied year. In addition, Provenzano (2020) has revealed the connections between states shaped by migration stocks and tourism flows. By using several econometric analyses, he has investigated the main determinants of the correlation patterns between the two networks.…”
Section: The Empirical Studiesmentioning
confidence: 99%
“…Ülkelerin kalkınma sürecinde ortak bir araç olarak kullanılan turizm sektörü, özellikle bilgi ve ulaşım teknolojilerindeki hızlı gelişim sayesinde ülke ekonomilerinin makro değişkenleri üzerinde de önemli etkiler yaratmaktadır. Hem gelişmiş hem de gelişmekte olan ülkelerin turizm hareketliliği incelendiğinde, sektördeki gelişmelerin milli gelir, istihdam ve vergi gelirlerini olumlu etkilediği ve ekonomik dengesizliklerinin azaltılmasında önemli rol oynadığı görülmektedir (Morley 1996;Balaguer ve Jorda, 2002;Yang ve Chen, 2009;Provenzano, 2020 Sağlık alanında kayıptan kaçınma üzerine yapılan önceki araştırmalar, göreceli olarak belirli sonuçlara odaklanmış (örneğin, sigarayı bırakmak sağlığı iyileştirecektir) ve küresel bir sağlık krizinde kayıp ve kazanç mesajlarının etkisine ilişkin araştırmalar, sokağa çıkma yasağı gibi müdahalelerin başlamasından önceki varsayımsal müdahalelere dayanıyordu (Hameleers, 2020). Bununla birlikte, birçok ülkenin COVID-19'un yayılmasını önlemek amacıyla sosyal mesafenin önemine vurgu yaptığı pandemi süresince; bu salgına yönelik risk algılarını beklenti teorisinin tersi yönünde şekillendirmek gerektiği anlaşılmıştır.…”
Section: Covid-19'un Turizm Sektörüne Etkisiunclassified